Matthew’s portrait of Jesus - Viljoen, FP (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
Studies in Matthean Christology often tend to focus merely on the titles given to Jesus in this Gospel. These titles are considered as KEY WORDS to convey the early Christians’ confession of Jesus. Such an approach holds the risk of assuming that Matthew had a worked out “Christology” and that these titles had universal and fixed meanings. In this article I argue that such titles provide helpful pointers to Matthew’s understanding of Jesus, but on condition that their meanings are carefully interpreted within the context of the Matthean narrative. One also has to read beyond the titles and recognize allusions and motifs which Matthew uses to present his compelling narrative of Jesus.